Mediasi Kebijakan Deviden pada Pengaruh Profitabilitas terhadap Nilai Perusahaan BUMN yang Listing Periode 2014-2018 - Sukirno Sukirno (Telaah Bisnis, 2021)
Profitability and dividend policy viewed with signaling theory has information content so that it can affect the value of the company. The purpose of this study is to examine the mediation of dividend policy on the effect of profitability on the value of listed SOEs in the 2014-2018 period. Research samples of 13 companies were taken using a purposive sampling technique with several criteria according to research needs. The research method uses a quantitative approach with simple regression analysis tools and sobel tests. This study shows that partially profitability has a significant effect on firm value, profitability has a significant effect on dividend policy, while dividend policy does not affect firm value. this study also shows that dividend policy cannot mediate the effect of profitability on firm value.